(untitled) (Gumilyov Journal of Pedagogy, 2026)
Virtual reality is a virtual world created on the basis of software that allows you to perceive a phenomenon or action through the senses. The research article examines the possibilities and risks, advantages and disadvantages of using virtual reality programs and methods in professional training of specialists. The relevance of the article is justified within the framework of programs that oblige to digitize all sectors of the country. The characteristics of the virtual reality device, as the most promising tool included in the modern educational sphere, will also be developed. To determine the level of virtual reality research, an analysis of the work of domestic and foreign scientists who studied it in various fields was carried out. As a result, the possibilities and some risks of using virtual reality have been identified. In the practical part of the article, in order to familiarize teachers with the possibilities of virtual reality, the Google Expeditions VR application will be presented to teachers, and the students of the experimental group will be given a psychodiagnostic technique through the Tilt Brush virtual reality application. After the experiment, the results of the students in the control and experimental groups were compared. A survey of teachers from various universities is also conducted in order to determine the importance of virtual reality in the professional education of students. As a result of the survey, most of the teachers expressed their willingness to teach using virtual reality. The conclusion of the general research work emphasizes that the use of virtual reality in vocational education is effective, but at the same time, there is a need to create high-quality professional educational content corresponding to the devices of virtual reality.